Separation and Spectroscopic Characterization of N-Paraffin Waxes and Isoparaffins from Three Local Crudes in Kurdistan Region of Iraq - Younis, Mohammed K.; Al-Ghulami, Firas S.; Saleem, Fanar M. (Science Journal of University of Zakho, 2013)
Samples of light, medium and extra heavy Kurdistan crude oils and have been de-asphalted and separated into fractions of saturates by elution liquid chromatography technique. The fractions obtained were separated into n-paraffins, isoparaffins by urea adduction and analyzed using FTIR spectroscopy. The infrared data confirmed the presence of methyl and methylene groups in the saturate fractions of the crude oils. Tawke paraffins fraction have highest value of methyl index, while Jamjamal have the lowest, it means that it has the longest chains of saturate hydrocarbon more than others, while Taqtaq isoparaffins have the highest value, Jamjamal has the lowest.